1964
DOI: 10.1136/bmj.2.5407.480
|View full text |Cite
|
Sign up to set email alerts
|

Relief of Post-operative Pain: Comparison of a 25% Nitrous-oxide and Oxygen Mixture with Morphine

Abstract: Nitrous oxide has had a wide use as an analgesic in midwifery and in dental surgery, but its use does not appear to have been investigated for the relief of post-operative wound pain.We describe here a study designed to compare the relative potency of nitrous oxide and morphine for relief of pain in patients during the first 48 hours after upper abdominal operations. Post-operative pain in such patients restricts breathing to a marked degree, and the relief by analgesics of this restriction can be assessed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1966
1966
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Lung function tests are widely used as objective criteria in clinical trials of analgesic drugs ( MASSON 1962( MASSON , 1964PARKHOUSE and HOLMES 1963 ;PARBROOK 1966, PARBROOK et al 1964CONAGHAN et al 1966;LOAN and DUNDEE 1967) and in investigations of placebo effects (PARKHOUSE 1963). However, such investigations are primarily concerned with the drugs to be tested and not with the relief of the patient's pain or improvement of the respiratory performance.…”
mentioning
confidence: 99%
“…Lung function tests are widely used as objective criteria in clinical trials of analgesic drugs ( MASSON 1962( MASSON , 1964PARKHOUSE and HOLMES 1963 ;PARBROOK 1966, PARBROOK et al 1964CONAGHAN et al 1966;LOAN and DUNDEE 1967) and in investigations of placebo effects (PARKHOUSE 1963). However, such investigations are primarily concerned with the drugs to be tested and not with the relief of the patient's pain or improvement of the respiratory performance.…”
mentioning
confidence: 99%
“…Early studies evaluating its potency in comparison with opioid analgesics reported that 30% nitrous oxide is equivalent to 10-15mg of morphine. 7,8 Entonox ® , a mixture of 50% nitrous oxide in oxygen, can be used in spontaneously breathing patients to provide analgesia for short duration procedures where pain is predictable.…”
Section: What Is Entonox ® and How Does It Work?mentioning
confidence: 99%
“…In the following section we have graded published evidence according to the widely recognised criteria described by Sackett et al 9 In 1964, Parbrook found that inhalation of 20%-25% N 2 O produced a similar analgesic potency to 10 mg-15 mg of intramuscular morphine. 10 [level of evidence 2b] In adults, N 2 O has been used for the reduction of fractures and joint dislocations. 11 12 [level 2b].…”
Section: Clinical Studiesmentioning
confidence: 99%